1971
DOI: 10.1021/jf60175a023
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizers for the accelerated degradation of chlorinated cyclodienes and other insecticide chemicals exposed to sunlight on bean leaves

Abstract: Rotenone and some related substituted-4-chromanones act as photosensitizers to accelerate the photoalteration of chlorinated cyclodiene insecticide chemicals exposed to sunlight on bean leaves. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…aldrin (15), endrin (19), isodrin (2/) and heptachlor (1), when exposed to sunlight on plant surfaces. 50 Major photo-products are produced as a result of photoisomerisation, except for compound 15, which also gives photodieldrin (18) in addition to photo-aldrin (16), as is evident from the following Scheme (IV):…”
Section: Rotenonementioning
confidence: 97%
See 1 more Smart Citation
“…aldrin (15), endrin (19), isodrin (2/) and heptachlor (1), when exposed to sunlight on plant surfaces. 50 Major photo-products are produced as a result of photoisomerisation, except for compound 15, which also gives photodieldrin (18) in addition to photo-aldrin (16), as is evident from the following Scheme (IV):…”
Section: Rotenonementioning
confidence: 97%
“…organophosphate compounds, methylcarbamates, pyrethroids and dinitrophenol derivatives, on plant surfaces using rotenone as sensitizer has been reported. 50 These sensitized photodegradations require a high rotenone level in most cases.…”
Section: Rotenone Bean Leaves •16+18mentioning
confidence: 99%
“…A possible means of regulating decomposition rates can be addition of a special sensitizer into a pesticide formulation to absorb the near-land sunlight followed by transfer of this energy to the pesticide molecules, which then should decompose. Several regulating chemicals have been experimented in 70-80 s, but, for some reasons, these sensitizers have found no practical use in plant protection [14,15,17,18,24]. The authors have earlier studied the photochemical interaction between several pesticide chemicals and sensitizers in the form of fine particles and thin films in the outdoor and laboratory conditions [25][26][27].…”
Section: Photodecomposition Of Pesticide Pollutants Relevant To Ambiementioning
confidence: 99%
“…It consists of naphthenic hydrocarbons (60% by weight), and 40% of polycyclic aromatics such as naphtalene, phenanthrene, and anthracene. These aromatics are well known as photo-sensitizers, and they were used for the induced photo-degradation (aging) of polymers [21,22], and for the regulating decomposition of pesticide residues [15,24]. The liquid naphthenic hydrocarbons serve here as a composite solvent that is suitable for dissolving the pesticide chemicals under study.…”
Section: Pesticide Chemicals and Analysis Techniquementioning
confidence: 99%
“…[1][2][3][4][5][6] Many researchers have examined its transformations on exposure to sunlight in air, 7) to sunlight in the presence of photosensitizer in air 8,9) or to UV at wavelengths longer than 290 nm in a vapor-phase system in air, 10) as well as in the presence of nitrogen dioxide in air, 11) in the presence of a-diketones including glyoxal, methylglyoxal and biacetyl in air, 12) in the presence of suspended particulates in air 13) and in the presence of benzaldehyde in air. 14) Interestingly, it was observed that crude 3 gave 4 in moderately yield when exposed to light at wavelengths longer than 290 nm.…”
mentioning
confidence: 99%